Sleep Habit/Sleepiness Questionnaires: A Useful Tool to Identify Correlation Between Sleep, Academic Performance and Obesity Promotion in Improving Health. (29th May 2020) - Gupta, Pratibha; Collins, Matt
Abstract: Objectives: Identify, compare sleep habit questionnaires for use in a study of college student's body compositions, and academic performances. Methods: Decades of research supports the importance of proper sleep habits for college students for optimum academic performances and maintaining a healthy lifestyle. Instrument that can identify students who experience sleep disturbances and who do not get enough sleep is important in preventing obesity in college students during their college experience and afterwords. Some surveys were created for the clinical setting to determine if further diagnostics testing is necessary, while others were designed for use in academic research to be used individually, combined into composite measure of sleep or as covariates. Available instruments measure many different variables from day time sleepiness to chronotype and jet-lag. No single survey stands out as an all -encompassing sleep different aspect of sleep. No cross comparison of instruments measuring the same variable is therefore possible. Sleep survey is considered ensuring that the chosen survey was designed to measure the variables of interest. Following scales were used in the study: Standford Sleepiness Scale, Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Horne-Ostberg Moringness Eveningness Questionnaire, Munich Chronotype Questionnaire. Results: Students not meeting public health recommendations for sleep quality and quantity were found to have a significantly lower grade point average and individuals with sleep disturbances and short sleep duration have a significantly higher incidence of obesity. Conclusions: Each instrument was created to measure a specific but different aspect of sleep. When conducting research with these tools, another questionnaire may be necessary to provide data specifically about the the subject's sleep habits. The Pittsburgh Sleep quality index has seen through use both clinically and in research. However, it requires another questionnaires to provide data on other variables. Each questionnaire effectively measures the concept it was designed to measure. Therefore, the choice of appropriate instrument should be based on the question, "which survey measures the variable that I wish to measure?", not which survey is the best? Funding Sources: NIMHD BRIC Grant 2009–2013 Central State University.